Study guides

☆☆

Q: How do you solve 6 -4?

Write your answer...

Submit

Related questions

2/3 +4/6 =

-4

12g-6=6+4=10g

how do i solve -3r+3r=-6(7+7r)-7(4-7r)

7 6 4 6 2 6 1 6

Since adding a negative is the same as subtracting a positive, 4+(-6) 4-6 -2

24x = 6 x = 6/24 x = 1/4

2/3+4/6

-18

6(y - 4)

-22

6 - 3x = 4 - 2x 6 = x + 4 x = 2 Check it. 6 - 6 = 4 - 4 It checks.

2/3 + 4/6 =4/6 + 4/6 =8/6 =4/3 or =1 1/3

6' 4"= 6-1/3 feet

x=4 x=4

3x - 4 = -2 The answer is x=2/3

-x=-2

-4

10

4 / 6 = 0.666667Converting decimal to a percentage: 0.666667 * 100 = 66.67%

6(n - 4)(n + 1) n = 4, -1

4a-2=7a-6 4=3a a=4/3

4 over 1 is 4. 2 + 4 is 6.

a + 4 = 10(a + 4) - 4 = 10 - 4a = 6

I will help.... You have to solve for x 1) simplify 2x-6=4 2) 2x=? 2) x=? Hint make 6 equal zero on the left side of the equation